Absolute or relative voice rest after phonosurgery: a blind randomized prospective clinical trial. (2nd October 2018) - Whitling, Susanna; Lyberg-Åhlander, Viveka; Rydell, Roland
Abstract: Objectives: The first aim, was to compare participant compliance with postoperative voice rest advice in two groups. The second aim was to compare vocal function and recovery in the short-term, seven days post-surgery and in the long-term, 3–6 months post-surgery. Design: Preliminary randomized prospective blind clinical trial. Methods: Twenty patients scheduled for surgery for benign vocal fold lesions were randomized into seven days of absolute or relative voice rest. Compliance with voice rest advice was monitored with a voice accumulator for seven days following surgery. Vocal recovery was tracked through (a) self-perceived vocal function, (b) perceptual assessments of voice recordings and (c) visual assessment of high resolution and high speed digital imaging (d) vocal stamina and reaction to vocal loading, explored with a vocal loading task. Results: The absolute voice rest group phonated significantly less than the relative voice rest group during seven days post-surgery, but they were not silent. The absolute voice rest group self-reported more difficulty with compliance than the relative voice rest group. The relative voice rest group coped with significantly more vocal loading at long-term check-up. In the short-term the absolute voice rest group improved morphological recovery to a significant degree, however relative voice rest renders superior long-term recovery. Conclusions: Absolute voice rest is difficult to comply with. Neither short-term, nor long-term vocal recovery differed significantly between groups. Within-group comparisons showed significant improvements in vocal stamina, immediate recovery from vocal loading and self-assessments of voice problems only for the group with recommended relative voice rest.